Low Prevalence of Factor V:Q506 in 41 Patients with Isolated Pulmonary Embolism - Martinelli, Ida; Cattaneo, Marco; Panzeri, Daniela; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1997)
In 70-80% of cases, pulmonary embolism is the consequence of lower extremity deep vein thrombosis. It has been demonstrated that the most common coagulation defect predisposing to venous thrombosis, resistance to activated protein C (APC), is not associated with an increased risk for pulmonary embolism, but the evidence was based on a functional assay to diagnose APC resistance and no information about concomitant deep vein thrombosis was provided. The aim of our study was to evaluate the prevalence of factor V:Q506, the gene mutation responsible for APC resistance, in patients with symptomatic non-fatal pulmonary embolism, whether or not associated with deep vein thrombosis. Patients with uncomplicated deep vein thrombosis and healthy controls were investigated as comparison groups. The overall prevalence of factor V:Q506 in 106 patients with pulmonary embolism was 12.3%, lower than that found in 106 patients with deep vein thrombosis (22.6%, OR 0.5, 95% Cl 0.2-1.0) but significantly higher than that found in 212 healthy subjects taken as controls (2.8%, OR 4.8,95% Cl 1.8-13.0). In the 41 patients with isolated pulmonary embolism, i.e., without the presence of deep vein thrombosis, the prevalence was 4.9%, similar to that in controls (OR 1.8,95% Cl 0.3-9.6), while in the remaining 65 patients with pulmonary embolism associated with deep vein thrombosis the prevalence was significantly higher (16.9%, OR 5.5, 95% Cl 2.0-15.8). In conclusion, the prevalence of factor V:Q506 is high in patients with pulmonary embolism associated with deep vein thrombosis, whereas in patients with isolated pulmonary embolism it is similar to that found in control subjects. This intriguing finding is of difficult interpretation and needs confirmation by further studies.